2021
DOI: 10.1002/cssc.202101089
|View full text |Cite
|
Sign up to set email alerts
|

Chlorides, other Halides, and Pseudo‐Halides as Additives for the Fabrication of Efficient and Stable Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) are attracting a tremendous attention from the scientific community due to their excellent power conversion efficiency, low cost, and great promise for the future of solar energy. The best PSCs have already achieved a certified power conversion efficiency (PCE) of 25.5 % after an unprecedented rapid performance rise. However, high requirements with respect to large area, high‐efficiency devices, and stability are still the challenges. Major efforts, especially for achieving a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 203 publications
0
11
0
Order By: Relevance
“…Moreover, the introduction of the ACN/MA/EtOH solvent system also results in a reduction in full‐width‐at‐half‐maximum (FWHM) value (0.169° vs 0.130°) for the (111) peak in contrast to the anti‐solvent one, which, according to the Scherrer equation, indicates a larger crystallite size. [ 52 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the introduction of the ACN/MA/EtOH solvent system also results in a reduction in full‐width‐at‐half‐maximum (FWHM) value (0.169° vs 0.130°) for the (111) peak in contrast to the anti‐solvent one, which, according to the Scherrer equation, indicates a larger crystallite size. [ 52 ]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the introduction of the ACN/MA/ EtOH solvent system also results in a reduction in full-widthat-half-maximum (FWHM) value (0.169° vs 0.130°) for the (111) peak in contrast to the anti-solvent one, which, according to the Scherrer equation, indicates a larger crystallite size. [52] The preferred orientation and crystalline quality of the antisolvent and the FSSG perovskite films were further investigated by the grazing incidence wide-angle X-ray scattering (GIWAXS) measurements, and the corresponding 2D patterns are displayed in Figure 3 and Figure S6, Supporting Information. The perovskite film fabricated from anti-solvent process exhibits a strong diffraction ring, indicating orientation randomness.…”
Section: Morphologymentioning
confidence: 99%
“…20 Therefore, organic chloride additives, such as methylammonium chloride (MACl) and formamidinium chloride (FACl), were applied in the perovskite precursor solutions to form the intermediate species and regulate the crystallization of perovskite films. 21,22 carrier transport by adding amino-functionalized carbon nanotubes and MACl. 23 Limited by the solubility of the MACl in the precursor, Yoon et al obtained highly uniform and pinhole-free CsPbI 3 perovskite films by sequentially dripping MACl solution to control the intermediate stages of the crystallization process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The additive engineering of perovskite precursor solutions has become one of the most promising strategies to improve the crystal quality and suppress defects of the CsPbI 3 perovskite films by forming intermediate complexes during the crystallization of the perovskite films. Yang et al found that the Cl – ions would benefit the nucleation of the perovskites without entering into the perovskite lattice, leading to perovskites with improved optoelectronic properties being obtained . Therefore, organic chloride additives, such as methylammonium chloride (MACl) and formamidinium chloride (FACl), were applied in the perovskite precursor solutions to form the intermediate species and regulate the crystallization of perovskite films. , Wang et al fabricated high crystalline uniaxial-orientated perovskite films with enhanced charge-carrier transport by adding amino-functionalized carbon nanotubes and MACl . Limited by the solubility of the MACl in the precursor, Yoon et al obtained highly uniform and pinhole-free CsPbI 3 perovskite films by sequentially dripping MACl solution to control the intermediate stages of the crystallization process .…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Generally, Cl additives are known to tune the film formation for perovskites, leading to improved morphology and high crystallinity, and consequently solar cell performance in most cases. [33] But the analysis of published literature showed that there are few studies dedicated to gaining a deeper insight into the underlying mechanisms behind the properties improvements using organic additives besides the popular MACl additive which should be avoided due to possible incorporation of MA into the host perovskite lattice capable of slightly blueshifting the bandgap in addition to its propensity to easily undergo thermal decomposition. [34] In this work, we investigate and compare EACl, PACl, and BACl additives and then double BACl-EACl additives for Cs 0.1 FA 0.9 PbI 3 films and PSCs.…”
Section: Introductionmentioning
confidence: 99%